THE CORRELATION BETWEEN HUSBAND SUPPORT AND THE USE OF INTRA-UTERINE DEVICE (IUD) IN WOMEN OF CHILDBEARING AGE: A META-ANALYSIS STUDY - Dewi Aulia Nuraini; Abdu Nafan Aisul Muhlis (Universitas Airlangga, 2021)
The rapid increase of population growth yearly is a problem that Indonesia generally faces. Various efforts to resolve this problem have been done by the government, one of which is the Family Planning Program and strategies for the use of contraception. Intra-Uterine Device (IUD) is one contraception type that remains unpopular, with only 6.6% of users in 2018. One of the factors assumed to affect the contraceptive use is spouse support. The aim of this study was to analyze and then summarize the findings on the correlation between husband support and the use of IUD in women of childbearing age. Ten studies with certain criterias that had been selected from various databases were used in the meta-analysis. The data were analyzed with the Comprehensive Meta-Analysis 2 trial version. Based on the analysis, husband support was a factor correlated with the use of IUDs in women of childbearing age (p = 0.000).